2021
DOI: 10.17221/48/2020-rae
|View full text |Cite
|
Sign up to set email alerts
|

Energy and exergy analyses of okra drying process in a forced convection cabinet dryer

Abstract: A forced convection automatic cabinet dryer integrated with a data logger was designed and fabricated. The okra samples were dried in the dryer at drying temperatures of 50, 60, and 70 °C and at three different load densities of 200, 300, and 400 g at a continuous air velocity of 0.7 m·s<sup>–1</sup>. Energy and exergy analyses of the drying process were performed. The obtained results showed that the energy efficiency, energy utilisation, and utilisation ratio increased from 26.59 to 68.24%, 5.47 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…Table 5 presents the mean exergetic sustainability index and varied from 1.12 to 1.63. Similar reports were reported by Okunola et al [54], Arslan and Aktas [37], and Beigi et al [40] for the exergetic sustainability index range for the drying of okra at 2.14 to 2.77, 1.07 to 1.21, and 1.05 to 1.42, respectively. As the value of the exergetic sustainability index is proportional to the exergy efficiency, the highest exergetic sustainability index values showed a slight impact on the environment, resulting in environmental imbalance and improvement of exergy efficiency.…”
Section: Exergetic Sustainability Indexsupporting
confidence: 87%
“…Table 5 presents the mean exergetic sustainability index and varied from 1.12 to 1.63. Similar reports were reported by Okunola et al [54], Arslan and Aktas [37], and Beigi et al [40] for the exergetic sustainability index range for the drying of okra at 2.14 to 2.77, 1.07 to 1.21, and 1.05 to 1.42, respectively. As the value of the exergetic sustainability index is proportional to the exergy efficiency, the highest exergetic sustainability index values showed a slight impact on the environment, resulting in environmental imbalance and improvement of exergy efficiency.…”
Section: Exergetic Sustainability Indexsupporting
confidence: 87%
“…This increase leads to enhanced energy utilization. Similar results were found for okra drying in a compulsory convection cabinet dryer [36], mushroom slices in convective drying [37], and cassava starch drying in a tray dryer [38], in which researchers reported that the greater the input air temperature, the greater the energy consumption.…”
Section: Energy Utilization (Eu)supporting
confidence: 70%
“…Therefore, to reduce this effect, the efficiency of exergy must be improved. Okunola, Adekanye and Idahosa [36] obtained an SI between 2.14 and 2.77. They reported that this value varies under the experimental conditions, and its value is proportional to the load density and has an inverse relationship with increasing temperature.…”
Section: Sustainability Index (Si)mentioning
confidence: 96%
See 2 more Smart Citations